Analisis Pengaruh Motivasi Kerja, Budaya Organisasi dan Gaya Kepemimpinan Transformasional terhadap Kinerja Aparatur Sipil Negara (Business and Accounting Education Journal, 2021)
The purpose of this study was to analyze the effect of motivation, organizational culture, transformational leadership style on the performance of state civil servants in the Banyumanik District Government, Semarang City. The population of this research is employees at the Banyumanik District Government Office, Semarang City, totaling 49 people and using a saturated sample. Data were collected by questionnaire and analyzed by multiple linear regression analysis. The results showed: 1) There was a simultaneous positive and significant influence between transformational leadership style, work motivation, organizational culture on employee performance in Banyumanik District, Semarang City. 2) There is no positive and partially significant effect between transformational leadership style variables on employee performance in Banyumanik District, Semarang City. 3) There is a partial influence between work motivation variables on employee performance in Banyumanik District, Semarang City. 4) There is a partial influence between organizational culture variables on employee performance in Banyumanik District, Semarang City.